PERANCANGAN SITE PLAN PENGEMBANGAN PARIWISATA PANTAI PULAU MAHORO DI KABUPATEN KEPULAUAN SITARO PROVINSI SULAWESI UTARA - Issabela A Lensehang; Bet El S. Lagarense; Aldy Adrianus Tatali (Jurnal Ilmu Pariwisata, 2022)
Tourism is one of the industry that uses of natural resources with high economic value to develop the region. Tourism development is required to strengthen management of natural resources in order to create touristic place. This movement is subjected to attract both domestic and foreign ourist. In addition to having higher economic values, tourism can also create and arouse the love to the country as well as boost the pride influenced acommunity’s deeper sense of care and belonging for their area. This study focus on the site plan design of beach tourism of Mahoro island in Sitaro Island Regency, North Sulawesi Province. The research used mixed method which combines qualitative and quantitave elements. The data analysis technique consists of some stages including editing, interpretation and beach tourism suitability formula. The results of this study showed that beach tourism of Mahoro Island in Sitaro Island Regency, North Sulawesi Province is one of the very potential attraction to be developed. Hoever, there are still many hindrances such as the absence of supporting facilities and infrastructures in the beach tourism of Mahoro Island, Sitaro Island regency, North Sulawesi.